2021
DOI: 10.3390/jmse9111292
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Seasonal and Spatial Variations of Coastal Water Quality Using Multivariate Statistical Techniques

Abstract: This study investigates the seasonal and spatial trends in Kuwait’s coastal water’s physical, chemical, and biological parameters by applying multivariate statistical techniques, including cluster analysis (CA), principal component/factor analysis (PCA/FA), and the Pearson correlation (PC) method to the average daily reading of water quality parameters from fifteen stations over one year. The investigated parameters are pH, turbidity, chlorophyll-a, conductivity, dissolved oxygen (DO), phycoerythrin, salinity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…This study observed that the spatial distribution of DO had the highest surface levels recorded in March in most coastal stations, while temperature and salinity were lower than in the offshore stations. In another study of Alkhalidi et al [39], Statistical Analysis was applied in order to investigate the relationships between coastal water parameters; and it confirmed the negative relationship between high WT and low DO levels, which were associated with the fish kill events that occurred during April and May 2017 in the Kuwait bay.…”
Section: Discussionmentioning
confidence: 81%
“…This study observed that the spatial distribution of DO had the highest surface levels recorded in March in most coastal stations, while temperature and salinity were lower than in the offshore stations. In another study of Alkhalidi et al [39], Statistical Analysis was applied in order to investigate the relationships between coastal water parameters; and it confirmed the negative relationship between high WT and low DO levels, which were associated with the fish kill events that occurred during April and May 2017 in the Kuwait bay.…”
Section: Discussionmentioning
confidence: 81%
“…Indicator bacteria are sensitive to sunlight; therefore, the time of day when samples are collected may significantly influence the final enumeration results (Hijnen et al, 2006; Pullerits et al, 2020). The spatial distribution of microbial pollution depends also on their susceptibility to salinity, DO, turbidity, CSOs discharge patterns, location of sources of pollutants, advection, and the distribution of mixing on the site (Alkhalidi et al, 2021; Cherif et al, 2019; Poopipattana et al, 2021). In general, the highest values of bacteria and the poorest water quality according to in situ measurements are recorded next to the river mouth, while lower values and better water quality status are observed moving away from the confluence of the river mouth with the sea (Cherif et al, 2019).…”
Section: How Do We Forecast Bathing Water Quality?mentioning
confidence: 99%
“…Pada suhu perairan yang tinggi dapat menyebabkan kelarutan DO menjadi rendah dan hubungan terjadi sebaliknya. (Wu et al, 2010, Alkhalidi et al, 2021 Berdasarkan grafik sebaran stasiun (Gambar 5) dapat dilihat pengelompokan stasiun. Stasiun 1, 2 dan 3 yang terletak di badan sungai dicirikan oleh parameter tingginya klorofil-a dan MPT.…”
Section: Active Variablesunclassified